Pemanfaatan Enzim Papain dalam Pembuatan Pakan Ikan Lele serta Pengolahan Nugget Ikan Lele - Deivy Andhika Permata; Sahadi Didi Ismanto; Alfi Asben (Warta Pengabdian Andalas, 2019)
Kelompok Muda Berkarya is a fisheries business group engaged in catfish farming. Issues incurred by partners are the costs incurred to buy pellets and slow growth of catfish. Besides that, the Kelompok Muda Berkarya and homemakers of fishers on Vilagge Pulau Karam are also interested in getting training on the manufacture of catfish processed products. However, there is no information on how to process it. Thus, improvement was carried out using counseling and demonstration methods, assistance, monitoring, and evaluation. From the results of the activities carried out, improving the understanding of fostered partners in making fish feed by adding papain enzymes and making catfish nuggets. The resulting pellets require low production costs and can be increased growth of catfish.